CRISPR-Cas9 Targeting of the eIF4E1 Gene Extends the Potato Virus Y Resistance Spectrum of the Solanum tuberosum L. cv. Desirée - Lucioli, Alessandra; Tavazza, Raffaela; Baima, Simona; Fatyol, Karoly; Burgyan, Jozsef; Tavazza, Mario (Frontiers in Microbiology, 2022)
Translation initiation factors and, in particular, the eIF4E family are the primary source of recessive resistance to potyviruses in many plant species. However, no eIF4E-mediated resistance to this virus genus has been identified in potato (Solanum tuberosum L.) germplasm. As in tomato, the potato eIF4E gene family consists of eIF4E-1, its paralogue eIF4E-2, eIF(iso)4E, and nCBP. In tomato, eIF4E-1 knockout (KO) confers resistance to a subset of potyviruses, while the eIF4E-1/2 double KO, although conferring a broader spectrum of resistance, leads to plant developmental defects. Here, the tetraploid potato cv. Desirée owning the dominant Ny gene conferring resistance to Potato virus Y strain O but not N was used to evaluate the possibility to expand its PVY resistance spectrum by CRISPR-Cas9-mediated KO of the eIF4E-1 susceptibility gene. After a double process of plant protoplast transfection-regeneration, eIF4E-1 KO potatoes were obtained. The knockout was specific for the eIF4E-1, and no mutations were identified in its eIF4E-2 paralogue. Expression analysis of the eIF4E family shows that the disruption of the eIF4E-1 does not alter the RNA steady-state level of the other family members. The eIF4E-1 KO lines challenged with a PVYN isolate showed a reduced viral accumulation and amelioration of virus-induced symptoms suggesting that the eIF4E-1 gene was required but not essential for its multiplication. Our data show that eIF4E-1 editing can be usefully exploited to broaden the PVY resistance spectrum of elite potato cultivars, such as Desirée, by pyramiding eIF4E-mediated recessive resistance.